2012
DOI: 10.1371/journal.pone.0040981
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of FKBP Inducible Degradation Domain Tagging Strategies for the Human Malaria Parasite Plasmodium falciparum

Abstract: Targeted regulation of protein levels is an important tool to gain insights into the role of proteins essential to cell function and development. In recent years, a method based on mutated forms of the human FKBP12 has been established and used to great effect in various cell types to explore protein function. The mutated FKBP protein, referred to as destabilization domain (DD) tag when fused with a native protein at the N- or C-terminus targets the protein for proteosomal degradation. Regulated expression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 32 publications
1
57
0
4
Order By: Relevance
“…However, the failure to generate transgenic lines where OPP/PSY would be expressed in fusion with the 15-kDa HA-DD24 tag suggested the protein levels expressed are insufficient, even in the presence of the stabilizing ligand Shld-1, or that its physiological function is lost when in fusion with the larger tag. In a previous study, it was shown that DD24 decreases the amount of fused proteins to a significant extent, which is not fully reversed by the presence of Shld-1 (26). We also attempted to generate a transgenic line expressing OPP/PSY in fusion with a 30-kDa GFP-HA tag, which should not affect its expression, but also failed (data not shown).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the failure to generate transgenic lines where OPP/PSY would be expressed in fusion with the 15-kDa HA-DD24 tag suggested the protein levels expressed are insufficient, even in the presence of the stabilizing ligand Shld-1, or that its physiological function is lost when in fusion with the larger tag. In a previous study, it was shown that DD24 decreases the amount of fused proteins to a significant extent, which is not fully reversed by the presence of Shld-1 (26). We also attempted to generate a transgenic line expressing OPP/PSY in fusion with a 30-kDa GFP-HA tag, which should not affect its expression, but also failed (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…To gather further proof that phytoene is essential and that PSY is the main target of squalestatin in the parasites, we attempted to overexpress OPP/PSY using a pEFbased vector (26), from which the gene would be under the control of the constitutive ef1-␣ promoter (39,40). It was expected that OPP/PSY would be overexpressed in the transfected parasites, since plasmids usually are maintained as concatemeric episomes of multiple copies.…”
Section: Effect Of Squalestatin On P Falciparum Carotenoid Biosynthementioning
confidence: 99%
“…Systematic testing of the DD and domains that are encoded by its various alleles has shown that degradation using this system is usually about fourfold when the compounds that stabilize the DD fusion protein are removed from the culture medium, with DD24 performing most reliably for carboxy-terminal fusion 90 . So far, the DD system has been used in P. falciparum to C-terminally tag the endogenous sequences of the cysteine protease calpain 91 , calcium-dependent protein kinase 1 (CDPK1) and CDPK5 (REFS 92,93), as well as DOC2.1, which possesses a calcium-dependent membrane-binding C2 domain 94 .…”
Section: Dominant Negative Transgenesmentioning
confidence: 99%
“…In order to overcome the potential toxicity of constitutive expression of J-GFP in transfected parasites, DD24, an FKBP12 mutant that previously showed optimal regulation of protein levels in NIH 3T3 cells [19] and in P. falciparum [20], was fused at the Cterminus of J-GFP to generate the fusion protein J-GFP-HA-DD24. The sequence encoding J-GFP-HA-DD24 was placed under the control of the strong constitutive bi-directional promoter ef1-α from P. berghei, which is also used to drive expression of the selectable marker gene human DHFR (dihydrofolate reductase) ( Figure 6A).…”
Section: Conditional Transgenic Expression Of J-gfp Causes Developmenmentioning
confidence: 99%
“…We have demonstrated in vitro that the J domain retains its ability to bind and inhibit the activity of full-length kinase even when fused to markedly larger polypeptides such as GFP. To inhibit endogenous CDPK1 in P. falciparum, we transfected the parasites with J-GFP N-terminally fused to the DD24 FKBP variant, which we have previously shown can routinely produce a 4-fold change in protein levels with or without Shld-1 in P. falciparum [19,20]. To reduce the potentially toxic effects of the J-GFP-DD24 protein during the transfection period, parasites were cultured without Shld-1 to decrease levels of the fusion protein.…”
Section: Introductionmentioning
confidence: 99%